The Relationship Between Workload and Work Stress of Nurses at the Jaury Jusuf Putera Academic Hospital, Makassar - Risnawati; Nurnainah; Abdullah; Normalia (Nursing Practice Journal, 2026)
High workloads for nurses have the potential to increase work stress, which can lead to decreased performance and quality of nursing services. Physical and mental demands, large numbers of patients, and shift work systems are factors that trigger psychological stress. This study aims to determine the relationship between workload and work stress among nurses at Jaury Jusuf Putera Academic Hospital in Makassar. This study used a descriptive correlational quantitative design with a cross-sectional approach. A sample of 42 nurses in the inpatient ward was taken using total sampling technique. Data were collected through a workload questionnaire and a work stress questionnaire, then analyzed using the Chi-Square test with a significance level of α = 0.05. The results showed that most nurses experienced moderate to heavy workloads and moderate levels of work stress. Bivariate analysis showed a significant relationship between workload and work stress (p < 0.05). In conclusion, the higher the workload of nurses, the higher the level of work stress they experienced. This study suggests that hospital management needs to implement proportional task distribution, evaluate the shift system, and provide psychological support and stress management programs. Effective workload management can improve nurses' well-being and the quality of nursing services